Revenue Generation and Its Consequences for Academic Capital, Values and Autonomy Insights from Canada - Eastman, Julia Antonia (OECD Publishing, 2007)
The greatest challenge for institutions of higher education in most OECD countries since the 1970s has arguably been to cope with reduced public support. Many institutions responded to reductions in funding, first, by cutting costs and lobbying governments to reverse cutbacks, and then - when it became clear that funding levels would not be restored - by seeking out new sources of revenue. Some institutions decentralised resource allocation in order to encourage units to generate non-government revenue. Recent research into the revenue generation strategies of Canadian universities suggests, drawing upon the work of Pierre Bourdieu, that such measures, while potentially effective in stimulating resource acquisition - and beneficial in other important respects - change internal values and conditions in ways that may ultimately undermine universities' autonomy, public credibility and capacity to create knowledge. Can leaders and managers enable their institutions to secure vital revenue, without diluting the values and conditions that have made universities unique and valuable to society? Can decision makers in government foster entrepreneurialism and responsiveness on the part of higher education institutions without compromising their raison d'être? This paper sheds light upon these questions